Modifying a cognitive behavioral suicide prevention treatment for adults with schizophrenia spectrum disorders in community mental health. (May 2022) - Bornheimer, Lindsay A.; Li Verdugo, Juliann; Holzworth, Joshua; Im, Vitalis; Smith, Fonda N.; Sliwa, Hannah; Taylor, Stephan F.; King, Cheryl A.; Florence, Timothy; Tarrier, Nicholas; Himle, Joseph A.
Highlights: Suicide is a critical public health issue among individuals with schizophrenia spectrum disorders. Community-based participatory research methods emphasize collaboration with community stakeholders and has potential to strengthen clinical outcomes and impact of community-based research. Logistic, perceptual, and clinical challenges are perceived by clients, peer advocates, and providers in the process of introducing a new evidence-based treatment innovation to practice. Abstract: Suicide is among the leading causes of death for adults with schizophrenia spectrum disorders. Given a paucity of evidence-based interventions tailored for psychosis, we sought to modify a promising Cognitive-Behavioral Suicide Prevention for psychosis (CBSPp) treatment for adults in US community mental health (CMH) settings using community-based participatory research methods. This article presents our modification methodology, stakeholder data and scholarly expert input, and CBSPp adaptations prior to future intervention testing. Stakeholder data ( n  = 25) were collected from clients, providers, and peer advocates in a CMH setting in Michigan. Findings were subsequently presented to a panel of scholarly experts in the fields of suicide and psychosis research, intervention research, and implementation science for input. Emerging themes from stakeholders include logistic, perceptual, and clinical challenges in the process of introducing this treatment in a CMH setting. Consistent with literature, buy-in and support for the delivery of a new treatment emerged as important factors in modifying and implementing CBSPp. A final modification list is presented in this paper and collaborations among stakeholders, researchers, and scholarly experts are essential to navigate psychosocial treatment innovation barriers with an overall goal of improving access, feasibility, and quality of this suicide prevention treatment.